2014
DOI: 10.1515/ijamh-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical fitness and obesity among a sample of adolescents in Cyprus

Abstract: Recent data revealed that adolescent obesity appeared to be a rising problem in Cyprus. However, there is a scarcity of published data regarding fitness-related parameters, which could contribute for the presence of obesity in Cyprus' adolescence population. The aim of the current study was to investigate the association between adolescent obesity, body composition, and fitness levels. A total of 270 high school students volunteered to participate in this cross-sectional study. Body mass and height were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
2
0
5
Order By: Relevance
“…Mak et al [ 17 ] claimed that the muscular endurance and flexibility of both boys and girls are positively correlated. Aphamis et al [ 36 ] asserted that a positive correlation exists between handgrip and vertical jump, and also 30 m sprint time and VO 2 max ( maximal oxygen uptake ) based on participants’ performance in strength tests. He et al [ 37 ] concluded that the performances of both sexes in hand grip strength, vertical jump, and sit-and-reach are significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Mak et al [ 17 ] claimed that the muscular endurance and flexibility of both boys and girls are positively correlated. Aphamis et al [ 36 ] asserted that a positive correlation exists between handgrip and vertical jump, and also 30 m sprint time and VO 2 max ( maximal oxygen uptake ) based on participants’ performance in strength tests. He et al [ 37 ] concluded that the performances of both sexes in hand grip strength, vertical jump, and sit-and-reach are significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la condición física, nuestro estudio muestra altos niveles de correlación inversa con los pará-metros de composición corporal. Estudios similares en adolescentes chipriotas muestran una asociación inversa entre tener una masa grasa alta y diferentes parámetros de condición física (27).…”
Section: Discussionunclassified
“…Physical fitness is associated with body adiposity in youth (Aphamis, Giannaki, Tsouloupas, Ioannou, & Hadjicharalambous, ; Tsiros et al, ). Previous findings indicated that cardiorespiratory fitness and body fat have independent relationships in predicting metabolic risk in adolescents (Silva et al, ).…”
Section: Discussionmentioning
confidence: 99%